К вопросу о синтаксической ортологии (применнтельно к построению сверхфразовых единств) - Драздаускас, А. (Kalbotyra, 1981)
The article deals with the orthological norms of written speech production in terms of sentence formattedness and the organization of supra-phrasal unities. The register of scientific prose is taken as the basis of analysis. Certain recommendations concerning the optimal division of scientific texts into supra-phrasal unities are suggested.